Analogias e modelagem no ensino de ciências - Paterlini, Norberto Carvalho Rocha (Universidade Federal de São Carlos, 2016)
We present a discussion about teaching practices, through the organization of courses and the structure of the curriculum, where the formalistic and Cartesian conception of mathematics is incorporated into the teaching of science, used not only as scientific language, but as a model for knowledge organization. The presence of the practice in the classroom is shy and most often used for justification, not for discovery. The overvaluation of the essence of the theories at the expense of its practical effects can ward off the interest of learners and result in the low scientific literacy that we observe the end of the education process. We intend to explore ways of alternative thoughts them the formalist one, and educational practice oriented for challenges, curiosity and discovery.
Keywords: Raciocínio analógico; Analogias; Práticas; Desafios; Analog reasoning; Analogies; Practices; Challenges; CIENCIAS EXATAS E DA TERRA